ANALISIS MANAJEMEN ARUS KAS SEBAGAI DASAR PENETAPAN KEPUTUSAN KEUANGAN PADA KEMAIU HAIRCARE - Rachma, Tika Dwi; Purwanto, Sugeng (KINDAI, 2025)
This study was conducted to understand cash flow management and its role as a basis for decision-making at Kemaiu Haircare, a small and medium-sized enterprise selling hair care products. The main issue examined is how cash flow is used as a basis for operational decisions, particularly regarding raw material purchases and funding promotional activities. The research method used is descriptive qualitative, with data collection techniques through interviews and analysis of Kemaiu's financial report documentation for the 2024 period. The analysis was conducted through processing cash flow statements, calculating the operating cash ratio, and earnings quality (Quality of Income). The results show that Kemaiu is able to maintain a stable cash flow performance. Cash inflow from online sales is able to cover a large portion of operational cash needs. Furthermore, cash flow serves as an important reference in managing inventory and allocating costs, thereby improving the effectiveness of management decision-making. Keywords: management, cash flow, decision making, finance